Perjanjian Bagi Hasil Ternak Babi Antara Kepala Desa dengan Masyarakat Menurut Kitab Undang-Undang Hukum Perdata di Desa Loborai Kecamatan Sabu Timur Kabapaten Sabu Raijua Provinsi Nusa Tenggara Timur - Petronela Haba Manu; Agustinus Hedewata; Petornius Damat (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The purpose of this study is to analyze the pig production sharing agreement between the Village Head and the community according to the Civil Code in Loborai Village, East Sabu District, Sabu Raijua Regency, East Nusa Tenggara Province. In the process of this research, the author uses empirical research methods with the aim of research to find out and describe various matters related to the implementation of the pig production sharing agreement in Loborai Village, East Sabu District which will provide benefits in the form of rational thinking in an effort to answer various problems related to the pig production sharing agreement in Loborai Village, East Sabu District. The results of the research show that the form of pig profit-sharing agreement carried out by the village head with the community is carried out in written and unwritten (oral) forms. The written agreement is carried out by the community in the form of an agreement in the division of profit sharing for pigs. Whereas in the oral form, the village head and the community make an agreement to raise pigs and the results of the livestock if they breed and have results from the pigs will be shared with the community to maintain the results of the pigs that have been given. If there is a problem in the pig profit-sharing agreement between the village head and the community in raising pigs, for example, in this case the community is negligent so that the pigs die, then the village head as the owner does not sue but is resolved properly. However, another thing that is absolute to note is that the agreement made and carried out must be in good faith.